1997
DOI: 10.1002/art.1780401217
|View full text |Cite
|
Sign up to set email alerts
|

Circulating plasma levels of nucleosomes in patients with systemic lupus erythematosus. Correlation with serum antinucleosome antibody titers and absence of clear association with disease activity

Abstract: Objective. To assess nucleosome plasma levels in patients with systemic lupus erythematosus (SLE) and to study the correlations with serum antinucleosome, anti-double-stranded DNA (anti-dsDNA), and antihistone antibody activities, as well as with disease activity (by the SLE Disease Activity Index [SLEDAI]).Methods. In a cross-sectional study, we assessed 58 SLE patients for their plasma nucleosome levels. Plasma nucleosome levels as well as serum antinucleosome, anti-double-stranded DNA, and antihistone antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
119
2
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 167 publications
(134 citation statements)
references
References 41 publications
12
119
2
1
Order By: Relevance
“…The DNA in SLE IIF could be of exogenous microbial origin or could be derived from endogenous dying cells. The latter possibility is supported by the presence of elevated levels of circulating apoptotic cells and DNA in the form of nucleosomes (25,26), an increased rate of apoptosis (27)(28)(29), and decreased clearance of apoptotic cells in SLE patients (30). We were also able to demonstrate that apoptotic cells combined with IgG purified from serum of SLE patients (SLE IgG) triggered IFN␣ production in normal peripheral blood mononuclear cells (PBMCs) (31).…”
mentioning
confidence: 79%
“…The DNA in SLE IIF could be of exogenous microbial origin or could be derived from endogenous dying cells. The latter possibility is supported by the presence of elevated levels of circulating apoptotic cells and DNA in the form of nucleosomes (25,26), an increased rate of apoptosis (27)(28)(29), and decreased clearance of apoptotic cells in SLE patients (30). We were also able to demonstrate that apoptotic cells combined with IgG purified from serum of SLE patients (SLE IgG) triggered IFN␣ production in normal peripheral blood mononuclear cells (PBMCs) (31).…”
mentioning
confidence: 79%
“…Indeed, high levels of circulating nucleosomes have been found in some patients with SLE (41). High titers of IgG against nucleosomal antigens were also found in 2 patients with a heterozygous nonsense mutation in exon 2 of DNase I (42).…”
Section: Discussionmentioning
confidence: 99%
“…Our data show that there does not appear to be any intrinsic functional defect of macrophages from young MRLϩ/ϩ mice to recognize and phagocytose apoptotic thymocytes. It is interesting to note that we found that challenge of macrophages from young MRLϩ/ϩ mice with nucleosomes (as a mimic of in vivo increased cell apoptosis in lupus) [18][19][20][21][22] markedly reduced their ability to phagocytose apoptotic cells. The inhibitory effect elicited by nucleosomes was almost achieved with low concentrations of the autoantigen, and was not a consequence of any cytotoxic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Increased rates of spontaneous cell apoptosis in vitro have been detected both in human and mouse models of SLE [18][19][20]. Thus, these defects in apoptosis could account for the presence of the elevated concentrations of nucleosomes found in the circulation of lupus patients [21,22]. This increase of nucleosomes might be further augmented in lupus patients if cells dying by apoptosis failed to undergo surface changes recognized by phagocytes or if there were an intrinsic defect in the capacity of the macrophages from affected individuals to clear apoptotic cells.…”
Section: Introductionmentioning
confidence: 99%